Review on nanofluids characterization, heat transfer characteristics and applications. (October 2016) - Raja, M.; Vijayan, R.; Dineshkumar, P.; Venkatesan, M.
Abstract: Nanofluids are attracting many researchers for their superior thermo-physical properties with no or low penalty in pressure drop. The review is made by considering different parameters which govern the nanofluids characteristics, heat transfer performance and its application. Maximum effort is taken to account the contributions of different researchers available in open literature on different aspects of nanofluids such as thermal conductivity, viscosity, experimental, numerical studies on heat transfer performances and applications of nanofluids. The intention of this review is to provide an overview of the most recent studies on nanofluid in the literatures. It will be very useful for the scientific community working on nanofluid to update their knowhow about the nanofluid.